Quantification of 10 steroid hormones in human saliva from Chinese adult volunteers. Issue 4 (April 2018) - Liu, Jian; Qiu, Xuemei; Wang, Daoming; Li, Yantao; Zong, Yang; Liu, Yichen; Zhang, Yue; Yang, Ping; Zuo, Yong; Yang, Huanming; Wang, Jian; Du, Yutao; et al.
Objective: This study was performed to investigate the effects of age and sex on 10 salivary steroid hormones and analyze the correlations between salivary and plasma hormones. Methods: The concentrations of 10 salivary steroid hormones in 1090 Chinese adult volunteers were examined using liquid chromatography–tandem mass spectrometry, and a related investigation was performed on the concentrations of salivary hormones in this population. Results: The concentrations of androstenedione (A4), 17α-hydroxyprogesterone (17-OHP), aldosterone (ALD), cortisone (COR), corticosterone (CORT), cortisol (F), progesterone (P), and testosterone were significantly different between men and women (Student's t-test). Differences in 17-OHP and ALD concentrations were highly significant between women in the follicular and luteal phases of their menstrual cycle (Student's t-test). Five salivary steroid hormones (17-OHP, A4, CORT, COR, and F) significantly decreased with increasing age (Kruskal–Wallis test). A high linear correlation between salivary and plasma 17-OHP, P, A4, and F were observed with obvious sex-related differences (Pearson's correlation, r > 0.7). Conclusions: Our results provide important knowledge regarding the descriptive characteristics of salivary hormones in relation to age and sex and their correlations with plasma hormones.